Assessment Of Quality Standards Of Supported Employment By In-House Job Coaches And Employees With Disabilities - Chu, Shi Wei (2019)
Quality standards of supported employment are established for individuals with disabilities in many developed countries. In Malaysia, however, there is still no assessment of quality standards since the beginning of supported employment 10 years ago. The purpose of this study is to assess the quality standards of supported employment by in-house job coaches and employees with disabilities based on a developed model of quality supported employment in Malaysia. The objectives are to assess quality standards from three key dimensions which are organization, job coach service and outcomes. Furthermore, the predictors of outcomes are identified. The correlations in the assessment between job coach and employee with disabilities are identified. A mixed method research design which includes primarily quantitative research methods as well as qualitative research methods was utilized to collect data from 16 companies which provides in-house job coaching services and employment to employees with disabilities. The sample of the study includes 173 in-house job coaches and 173 employees with disabilities. A Quality Standards Framework for Supported Employment in Malaysia (QSFM) was operationalized into the Quality Supported Employment (QSE) Instrument for the purpose of the assessment. The results of the study indicated that the organizations surveyed were of the view that the quality standards of supported employment were good. Findings also included predictors of quality outcomes of supported employment which were the management and leadership of the organization, the intensive support at the workplace and follow-up services.